The rate of preeclampsia incidence in early pregnancy - Laras Ayu Pramesti; Fadil Hidayat (Science Midwifery, 2023)
Preeclampsia is the leading cause of morbidity and mortality in mothers during perinatal period, accounted for 70.000 mother deaths and 500.000 fetal death reported each year. Adolescent have not been set as the risk factor in guidelines to develop preeclampsia due to inconsistencies in literature findings. This study is a cross-sectional study which aims to find the incidence rate of preeclampsia and its complications in adolescent pregnancy located in Ciawi Regional Hospital during 2014-2016. This study involved patients aged 15-20 years old with complication of hypertension in pregnancy. This study found that 102 pregnant mothers with hypertension complication and 69 of them (67,6%) diagnosed as preeclampsia. Neonatal complication found in this study were 14,5% low-birth weight, 2,9% high-birth weight, and 26,1% IUFD. Maternal complication found were 24,6% preterm delivery, 2,9% post-term delivery, two patients (2%) with anemia, and one patient (1%) with uterine inertia, uterine rupture, and decompensated cordis. More than half of the sample in this study population were diagnosed with preeclampsia followed with various maternal and neonatal complications.